Malay proverb e-learning system with gamification for children / Muhammad Ridhwan Mohamad Munir - Mohamad Munir, Muhammad Ridhwan (2021)
This project focusses on the development of the Malay Proverb E-Learning system that is integrated with gamification. The system was designed and developed using the web-based applications such as the MYSQL as the database, HTML,JAVASCRIPT, CSS, and PHP as the programming language and Apache web server, with multimedia tools to facilitate e-learning in graphical representations. Gamification is a new concept. It is still not been taken seriously in academic studies and research. It has been defined as the use of gaming elements and mechanics in the non-gaming system. This paper discusses more closely the strategies appropriate for education throughout e-learning and introduces a template that defines the development of the educational gamification system. The implementation of gamification in e-learning was rendered in line with the structure suggested in this paper. The development of the system involves five phases of methodology which are Project Planning, Project Requirements, Project Designing, Project Development, and Project Documentation. At the end of the system development, series of usability and user acceptance tests were conducted to evaluate whether the E-Peribahasa system is helpful to improve children’s knowledge about Malay Proverb. As a result, the system is able achieved all the objective of this project and creating an enjoyable learning environment for the children to learn Malay proverb.